Comparative Effects of Phenolic Extract As an Ointment Dosage Form in Inducing Wound Healing in Mice and β-sitosterol in Experimentally Induced Acute Wound Healing in Mice (Journal of Pharmaceutical Negative Results, 2022)
Background: Wound healing is a multi-phase and well-organized dynamic process involving the coordinated use of numerous cell types and biological processes to repair damaged tissue, which relies on many inter-related factors. The failure of traditional healing protocols in many cases of acute wound healing that may progress to gangrene or lead to chronic wounds and amputation provides a strong stimulus to discover a neoteric, relatively long-term, safe, and effective treatment. Antioxidant, anti-inflammatory, and anti-microbial mechanisms are used. As is widely known, plant secondary metabolites such as phenolic compounds, besides their beneficial impact on the plant host, can be effective for humans in treating a variety of disorders. The most common properties of polyphenols—antioxidant, anti-inflammatory, and antimicrobial—indicate that they deserve recognition in natural medicine and may be highly effective in the treatment of various skin problems. Those three mentioned properties constitute the main potential mechanisms of action against various skin disorders.Aim: To compare the effects of phenolic extract from Iraqi Petroselinum crispum to β-sitosterol on wound size reduction, histological outcome, and biomarkers of collagen III, and epidermal growth factor, as well as identify the most likely mechanism of action in experimentally induced acute wounds in mice.Methodology: Phenolic compounds are extracted from Iraqi petroselinum crispum plants by universal methanol (80%) solvent, followed by fractionation by ethyl acetate to obtain phenolic compounds. The dose of phenolic compound will be (13,22%) w/w of extract and the phenolic extract powder mixed with Vaseline to obtain the ointment. In vivo study: Fifty male albino mice were enrolled in this study, and they were divided into five groups (N = 10/group). Group I: served as normal control. Group II served as an induced control, receiving only a petrolatum base (negative control).Mice with induced wounds were treated topically with β-sitosterol ointment (0.25% w/w) as a standard drug (positive control). Group IV and V: mice with induced wounds were treated topically with a phenolic extract of Petroselinum crispum ointment (13% and 22%w/w). respectively These products were applied twice daily for 10 consecutive days.Results: Phenolic extract ointment produced a highly significant reduction in wound size in comparison with petrolatum base (P≤0.001).In this histological study, re-epithelization and angiogenesis scores of all treatment groups showed a significant increase in comparison with the petrolatum base group (P≤0.05), but in collagen scores, the significant increase just occurred with the highest concentration of phenolic extract ointment (22% w/w) in comparison with the petrolatum base group (P≤0.05). In cytokine outcome at the end of the experiment, phenolic extract from petroselinum crispum (22% w/w) groups produced a significant increase in epidermal endothelial growth factor. Phenolic extract from petroselinum crispum (22%) produced a significant increase in collagen III in comparison with the β-sitosterol group (Pc≤0.05).Conclusion: According to the present findings, we can conclude that phenolic extract from petroselinum crispum ointment is more efficient than petrolatum base and comparable in efficacy to β-sitosterol ointment in accelerating wound healing.